AN EXPLORATORY STUDY OF CYBERBULLYING AND PERSONALITY TRAITS AMONG UNIVERSITY GRADUATES (The Research of Medical Science Review, 2025)
The widespread significance and deplorable rise of cyberbullying seriously jeopardizes psychological health, and emotional and physical well-being, particularly within the educational environment in this era. There is a dearth of research on the university population that elucidates the victim experiences from unavoidable cyber incidents. The present research aims to explore the relationship between cyberbullying and personality traits such as openness to experience, contentiousness, extraversion, agreeableness, and neuroticism in the context of university students. Method: The study employed quantitative methodology and the selected sample was 300 undergraduate students from the age ranges 18 to 29 years selected through convenient sampling techniques from various universities in Lahore. Furthermore, the statistical analysis involved correlation observed the relationship between personality traits measured through the Big Five Inventory Scale (1) and cyberbullying from the Cyberbully/Victim scale (2). Result: It was found that extraversion and openness to experience personality traits (E and O) were significantly correlated with cyberbullying in academic settings. Certain personality profiles have a likelihood to become easy targets of cyber harassment. Conclusion: The research addresses the need and value of counseling centers on campuses to ensure psychological support services that should be offered to students during cyberbullying situations. The aforementioned factor underlines the crucial role of educational awareness, law enforcement actions, anti-cyberbullying preventive measures, and university policymaking in creating a safer virtual atmosphere for students.